Impact cutoff frequency: Momentum scaling law inverted from Apollo seismic data - Gudkova, T.; Lognonné, P.; Miljković, Katarina; Gagnepain-Beyneix, J. (Elsevier, 2015)
© 2015 Elsevier B.V. We perform the analysis of both long and short period data for 40 large meteoroid impacts event gathered by the Apollo lunar seismic network. We extract the linear momentum released by the impact and the cutoff frequency of the recorded seismic spectrum, related to the radiation process of the shock wave generated by the impact. By using a proxy to the local porosity, based on the density of surface craters and well correlated to the most recent GRAIL observations, we demonstrate that the seismic cutoff frequencies for 40 selected impacts correlate with this proxy and therefore likely with the porosity at the impacted areas. Our finding shows that lunar seismic records of meteoroid impacts represent unique geophysical data documenting medium to high-energy (0.1-1 kt TNT yield) impact processes, including the interaction of shock waves with porous media. This work can be applied to the analysis of the seismic data to be obtained by the InSight mission in 2016 and the investigation of the lateral variations in the Martian regolith.